Being Part of an Editorial Board: Implications and Scope for Scientific Communication and Personal Academic Development - Barría P., R. Mauricio (Investigación y Educación en Enfermería, 2024)
Objective. From my experience as a member of the editorial board of the journal Investigación y Educación en Enfermería, the implications and scope of participating in this entity and the mutual and reciprocal benefits of this academic interaction between members of the editorial board and the journal are explained. Content synthesis. The key elements on operation, integration, tasks, and responsibilities of editorial boards to disseminate scientific research in different disciplines are analyzed and described, highlighting the rigor and commitment to academic ethics that allows guaranteeing the credibility of the contents published and topics addressed by a journal within a context of high competitiveness and risk of breaches of academic and scientific probity and ethics. Conclusion. Integrating an editorial board requires developing a fundamental role that implies a series of commitments and challenges that must be addressed with professionalism and ethics to guarantee the quality and prestige of the academic publication. In this task, achievements and goals are reached for the journal, as well as academic benefits for the editorial board members.